2015
DOI: 10.1134/s0020168515080105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, and properties of Ca3Co3.85M0.15O9 + δ (M = Ti–Zn, Mo, W, Pb, Bi) layered thermoelectrics

Abstract: We have prepared Ca 3 Co 3.85 M 0.15 O 9 + δ (M = Ti-Zn, Mo, W, Pb, Bi) solid solutions, investigated their crystal structure and microstructure, assessed their thermal stability in air, and measured their thermal expansion, electrical conductivity, and thermoelectric power in air at temperatures from 300 to 1100 K. The results demonstrate that the Ca 3 Co 3.85 M 0.15 O 9 + δ cobaltites are p type semiconductors and that their unit cell parameters decrease with an increase in the number of d electrons in the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
4
8
1
Order By: Relevance
“…It has been reported that partial substitutions with Fe and Ni for Co in Ca 3 Co 4 O 9 may increase the electrical conductivity by increasing the holes concentration from the conductive layers, provided that Fe and Ni take the usual oxidation states (2+) and/or (3+) [ 33 , 46 ], smaller than that of the mean Co valence responsible for the good electrical conductivity from this material, between (3+) and (4+) [ 29 ]. This fact was observed for small substitutions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that partial substitutions with Fe and Ni for Co in Ca 3 Co 4 O 9 may increase the electrical conductivity by increasing the holes concentration from the conductive layers, provided that Fe and Ni take the usual oxidation states (2+) and/or (3+) [ 33 , 46 ], smaller than that of the mean Co valence responsible for the good electrical conductivity from this material, between (3+) and (4+) [ 29 ]. This fact was observed for small substitutions.…”
Section: Introductionmentioning
confidence: 99%
“…The values of electrical conductivity and coefficient of thermo-EMF of ceramics, in the whole, were increased at increasing of the cobalt oxide content in the samples ( Table 5). The values of the apparent activation energy of electrical conductivity of the samples of A serie varied within 0.069-0.081 eV, which is typical for ceramics based on the layered calcium cobaltate [12,14,16] (excluding the samples having Ca 3 Co 3.8 O 9+δ , Ca 3 Co 4 O 9+δ composition, which had been sintered at 970°С, whose E A values were equal to 0.274 and 0.125 eV respectively and were abnormally high, which was probably due to the peculiarities of their microstructure).…”
Section: Results and Their Discussionmentioning
confidence: 88%
“…The values of the apparent activation energy of electrical conductivity of the samples of N serie varied within 0.050-0.072 eV, which is typical for ceramics based on the layered calcium cobaltate [12,14,16], slightly depended on the cationic compostiton of the samples and temperature of their sintering, and were less than for the samples which had been sintered in air or in oxygen.…”
Section: Results and Their Discussionmentioning
confidence: 91%
See 2 more Smart Citations